Therapeutic Response Monitoring in Chronic-Phase Chronic Myeloid Leukemia Treated with Tyrosine Kinase Inhibitors: A Narrative Review - Ngakan Ketut Wira Suastika; Ketut Suega (Fakultas Kedokteran Universitas Muslim Indonesia, 2026)
Background: Therapeutic response monitoring is essential in chronic-phase chronic myeloid leukemia (CML) treated with tyrosine kinase inhibitors (TKIs), as it guides the evaluation of treatment efficacy, detection of inadequate response, and individualized treatment decisions. Methods: This narrative review summarizes the current approaches to response monitoring in chronic phase CML treated with TKIs, focusing on hematologic, cytogenetic, and molecular assessments. Particular attention is given to BCR::ABL1 monitoring, response milestones, mutation-guided treatment decisions, and implementation challenges in resource-limited settings, including Indonesia. Results: Hematologic response is an early and accessible indicator of treatment activity, whereas cytogenetic assessment is useful for evaluating Philadelphia chromosome-positive cells and detecting additional chromosomal abnormalities. Molecular monitoring using quantitative BCR::ABL1 transcript measurement on the International Scale is the most sensitive method for assessing residual disease, defining treatment milestones, identifying warning or unfavorable responses, and selecting patients who may be considered for treatment-free remission (TFR). However, access to standardized molecular testing remains limited in many low- and middle-income countries because of costs, geographic disparities, laboratory infrastructure constraints, and health-system barriers. Practical strategies include prioritizing molecular testing at key milestones, strengthening referral laboratory networks, using automated platforms where feasible, supporting patient adherence, and developing clinical registries. Conclusion: Integrated resource-adapted response monitoring is crucial for optimizing TKI therapy in chronic-phase CML and reducing disparities in long-term outcomes.